2018
DOI: 10.3389/fimmu.2018.00302
|View full text |Cite
|
Sign up to set email alerts
|

The Immunomodulatory Effects of Macrolides—A Systematic Review of the Underlying Mechanisms

Abstract: BackgroundThe mechanisms underlying the non-antimicrobial immunomodulatory properties of macrolides are not well understood.ObjectivesTo systematically review the evidence for the immunomodulatory properties of macrolides in humans and to describe the underlying mechanism and extent of their influence on the innate and adaptive immune system.MethodsA systematic literature search was done in MEDLINE using the OVID interface from 1946 to December 2016 according to the preferred reporting items for systematic rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
206
1
13

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 233 publications
(233 citation statements)
references
References 81 publications
(77 reference statements)
1
206
1
13
Order By: Relevance
“…However, data on the efficacy of macrolide treatment are controversial. Two recent systematic reviews concluded that there is insufficient evidence to draw conclusions about the efficacy of macrolides in the treatment of M. pneumoniae lower RTIs in children, despite the fact that there is considerable evidence on anti-inflammatory properties of these agents (26)(27)(28). Interestingly, in our study, no short-term treatment benefit such as reduced oxygen requirement or shorter hospital stay was found when comparing patients with empiric administration of a macrolide and those with prescription 48 hours later after M. pneumoniae infection had been confirmed by nucleic acid amplification testing.…”
Section: Discussionmentioning
confidence: 99%
“…However, data on the efficacy of macrolide treatment are controversial. Two recent systematic reviews concluded that there is insufficient evidence to draw conclusions about the efficacy of macrolides in the treatment of M. pneumoniae lower RTIs in children, despite the fact that there is considerable evidence on anti-inflammatory properties of these agents (26)(27)(28). Interestingly, in our study, no short-term treatment benefit such as reduced oxygen requirement or shorter hospital stay was found when comparing patients with empiric administration of a macrolide and those with prescription 48 hours later after M. pneumoniae infection had been confirmed by nucleic acid amplification testing.…”
Section: Discussionmentioning
confidence: 99%
“…Azithromycin, a macrolide antibiotic, has long been touted for its anti-inflammatory effect and has been used as adjunctive therapy in treatment of community acquired pneumonia and chronic obstructive pulmonary disease exacerbations (147). Limited data suggest that adjunctive azithromycin in moderate-severe ARDS is associated with improved outcomes (148).…”
Section: Azithromycinmentioning
confidence: 99%
“…The diagnosis of CLAD is an indication to treat patients with an immunomodulatory macrolide. As such, even if the absolute number of patients receiving macrolides at our institution during the first year after lung transplantation is low, a bias of such treatment for cytokine distribution in BAL cannot be excluded [54]. Fifth, statistical methods were not used to adjust for storage time of the BAL samples, number of analyses per patient and date of collection after transplantation.…”
Section: Discussionmentioning
confidence: 99%